2018
DOI: 10.1161/hypertensionaha.117.10596
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy Lowers Incident Atrial Fibrillation in Primary Aldosteronism Patients at Long Term

Abstract: Primary aldosteronism (PA) causes cardiovascular damage in excess to the blood pressure elevation, but there are no prospective studies proving a worse long-term prognosis in adrenalectomized and medically treated patients. We have, therefore, assessed the outcome of PA patients according to treatment mode in the PAPY study (Primary Aldosteronism Prevalence in Hypertension) patients, 88.8% of whom were optimally treated patients with primary (essential) hypertension (PH), and the rest had PA and were assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 40 publications
1
101
0
1
Order By: Relevance
“…2,3 These risks can be mitigated either by resection of an aldosterone-producing adenoma (APA) by unilateral adrenalectomy or by effective blocking of mineralocorticoid receptors with normalisation of plasma renin levels in nonsurgical cases such as in patients with bilateral hyperplasia (BAH). 4,5 Therefore, to select the most appropriate treatment for each patient, the localisation of the source of aldosterone excess must be established. The most appropriate way to differentiate APA or predominant adenoma which would benefit from adrenalectomy from bilateral BAH remains the adrenal veins sampling (AVS), since adrenal imaging by computed tomography (CT) or magnetic resonance imaging (MRI) provides poor specificity for identifying lateralized PA. 1,6 However, AVS is an invasive and technically challenging procedure that is actually performed only in selected patients even at referral centres 7,8 and its usefulness has been challenged.…”
mentioning
confidence: 99%
“…2,3 These risks can be mitigated either by resection of an aldosterone-producing adenoma (APA) by unilateral adrenalectomy or by effective blocking of mineralocorticoid receptors with normalisation of plasma renin levels in nonsurgical cases such as in patients with bilateral hyperplasia (BAH). 4,5 Therefore, to select the most appropriate treatment for each patient, the localisation of the source of aldosterone excess must be established. The most appropriate way to differentiate APA or predominant adenoma which would benefit from adrenalectomy from bilateral BAH remains the adrenal veins sampling (AVS), since adrenal imaging by computed tomography (CT) or magnetic resonance imaging (MRI) provides poor specificity for identifying lateralized PA. 1,6 However, AVS is an invasive and technically challenging procedure that is actually performed only in selected patients even at referral centres 7,8 and its usefulness has been challenged.…”
mentioning
confidence: 99%
“…Moreover, the occurrence of LVH, LV fibrosis, impaired diastolic function, atrial dilatation and electric remodeling in PA (rev in [38]) explains why these patients were found to have a 12-fold higher risk of developing atrial fibrillation, the most common arrhythmia worldwide, than essential hypertensive patients in a French retrospective study [39]. Accordingly, adrenalectomy was found to lower the risk of atrial fibrillation in PA patients in the long-term longitudinal phase of the PAPY study [33]. Collectively these evidences support the concept that aldosterone favors atrial fibrillation [38] and that PA patients are more susceptible to heart failure with onset of atrial fibrillation [13,40] because of a 'stiffer' LV causing LV diastolic dysfunction and fibrosis, which lead to a greater dependency of the LV on the atrial kick for its filling.…”
Section: Cardiovascular and Renal Damage Associated With Pamentioning
confidence: 98%
“…In 1996, at a time when PA was still regarded as a 'benign' form of arterial hypertension, we reported that PA patients developed more left ventricular (LV) hypertrophy (LVH) than age-, sex-and BP-matched essential hypertensive patients, [32] and that this was particularly evident in those who showed more florid PA phenotypes due to an APA [13]. These findings were thereafter extended to show that they are more prone to develop fibrosis, atrial fibrillation [33], vascular remodeling [34], endothelial dysfunction [35,36], increased carotid intima-media thickness and femoral pulse wave velocity, more frequently than those with essential hypertension [13,14,32,37].…”
Section: Cardiovascular and Renal Damage Associated With Pamentioning
confidence: 99%
“…Although there is controversy over whether adrenalectomy is superior to adequate medical treatment with regard to cardiovascular outcomes, lines of recent evidence from observational studies speak to the superiority of surgical treatment in unilateral disease (9,12,13,14,15,16). For example, Rossi et al showed a higher risk of atrial fibrillation in medically treated versus adrenalectomized PA patients (17) and in a study done by Strauch et al arterial stiffness was reduced significantly by adrenalectomy but not after 1 year of spironolactone treatment (14). Moreover, a nationwide survey in Japan showed greater improvement of hypertension and hypokalemia in surgically treated PA patients compared to medical treatment with spironolactone (13).…”
Section: Types Of Primary Aldosteronism and Treatment Optionsmentioning
confidence: 99%